Plasma-Based Longitudinal Evaluation of ESR1 Epigenetic Status in Hormone Receptor-Positive HER2-Negative Metastatic Breast Cancer - Gerratana, Lorenzo; Basile, Debora; Franzoni, Alessandra; Allegri, Lorenzo; Viotto, Davide; Corvaja, Carla; Bortot, Lucia; Bertoli, Elisa; Buriolla, Silvia; Targato, Giada; Da Ros, Lucia; Russo, Stefania; et al. (Frontiers in Oncology, 2020)
Background: Endocrine therapy (ET) is the mainstay of treatment for hormone receptor positive HER2 negative metastatic breast cancer, however, adaptive mechanisms emerge in about 25-30% of cases through alterations in the estrogen receptor ligand-binding domain, with a consequent ligand-independent ER activity. Epigenetic-mediated events are less known and potentially involved in alternative mechanisms of resistance. The aim of this study was to test the feasibility of ESR1 epigenetic characterization through liquid biopsy and to show its potential longitudinal application for an early ET sensitivity assessment. Methods: A cohort of 49 women with hormone receptor positive HER2 negative MBC was prospectively enrolled and characterized through circulating tumor DNA using methylation specific droplet digital PCR (MS-ddPCR) before treatment start (BL) and after 3 months concomitantly with computed tomography (CT) scan restaging (EV1). ESR1 epigenetic status was defined by assessing the methylation of its main promoters (prom A and B). The most established ctDNA factors associated with ET resistance (ESR1 and PIK3CA mutations) were assessed through NGS. Associations were tested through Mann–Whitney U test, matched pairs variations through Wilcoxon signed rank test and survival was analyzed by log-rank test. Results: The ET backbone was mainly based on Aromatase Inhibitors (AIs) (70.83%) in association with CDK4/6 inhibitors (93.75%). Significantly lower promA levels at baseline were observed in patients with liver metastases (P=0.0212) and in patients with ESR1 mutations (P=0.0091). No significant impact on PFS was observed for promA (P= 0.3777) and promB (P = 0.7455) dichotomized at the median while, a ≥2-fold increase in promB or in either promA or B at EV1 resulted in a significantly worse prognosis (respectively P = 0.0189, P = 0.0294). A significant increase at EV1 was observed for promB among patients with PIK3CA mutation (P = 0.0173). A trend was observed for promB in ESR1 wild type patients and for promA in the ESR1 mutant subgroup. Conclusions: The study proofed the concept of an epigenetic characterization strategy based on ctDNA and capable to be integrated in the current clinical workflow to give useful insights on treatment sensitivity.